Media Pembelajaran Instalasi Listrik Rumah Tinggal Berbasis Pengendali Wireless - Salit Ngurah Bagus Alit Suyasa, Salit; Nyoman Santiyadnya; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2023)
This study aims to create learning media for residential electrical installations based on wireless controllers, to determine the feasibility of learning media to be applied to electric lighting installation subjects, to determine student responses to learning media for residential electrical installations based on wireless controllers at SMK Negeri 1 Denpasar. The research method used is research and development Research and Development (R&D). The results of the study showed that the validation results of content experts with very decent qualifications, the validation results of media experts with very decent qualifications, and the results of the small group test and also the large group test. The results of this learning media research are the results of the validation of content experts with a score of 90% with very decent qualifications, the results of the validation of media experts with a score of 95.83% with very decent qualifications, and the results of the small group test with a score of 100% and the very high category and also the large group test with a score of 100% and the very high category.